PEMANFAATAN LIMBAH BATOK KELAPA DAN KAYU ULIN UNTUK PRODUK PERHIASAN WANITA - Cindy Ayu Citra; Ramadhan S. Pernyata; Andi Farid Hidayanto (Indonesian Society of Applied Science, 2022)
The development of a modern, dynamic, and fashionable lifestyle, Jewelry was born in the midst of human life, especially for women. Jewelry is a trinket or decoration that has a function as a tool to beautify or beautify oneself to make it look more attractive. The problem at this time is the lack of utilization of coconut shell and ironwood waste which is only burned or thrown away. The purpose of making this product is to utilize coconut shell and ironwood waste material into a jewelry product that has selling value and aesthetic value. This product design method starts from alternative sketches, developing selected designs to become final designs or final designs, with research methods through data obtained from questionnaires, until the final results of jewelry designs are obtained from coconut shell waste and wood with a wood connection system with glue, with finishing using varnish that shows the natural color of coconut shell and ironwood, which is brown. So the conclusion of this design is the design of jewelry from coconut shell waste and ironwood that can be used and has aesthetic value and selling value.